2016
DOI: 10.3109/23744235.2016.1168937
|View full text |Cite
|
Sign up to set email alerts
|

Best oral empirical treatment for pyelonephritis in children: Do we need to differentiate between age and gender?

Abstract: This study recommends piv-mecillinam or amoxicillin-clavulanate as empirical treatment of first time pyelonephritis in Danish children from 6 months of age. Age and gender of patients should be taken into consideration when initiating empirical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
10
1
1
Order By: Relevance
“…From the published results, it seems that the regimen for AUP in adults should be P-MEC ≥400 mg tid (adjusted for weight) for at least 14 days in adults with/without initially IV MEC. Both clinical 33 and retrospective data on resistance rates 41 support a recommendation of P-MEC in pediatric pyelonephritis, administered as 25–40 mg/kg/day bid / tid for 10 days. 33 …”
Section: Discussionmentioning
confidence: 82%
“…From the published results, it seems that the regimen for AUP in adults should be P-MEC ≥400 mg tid (adjusted for weight) for at least 14 days in adults with/without initially IV MEC. Both clinical 33 and retrospective data on resistance rates 41 support a recommendation of P-MEC in pediatric pyelonephritis, administered as 25–40 mg/kg/day bid / tid for 10 days. 33 …”
Section: Discussionmentioning
confidence: 82%
“…Pivmecillinam is recommended for empiric therapy of UTI in adults and children in many places in Northern Europe [51,53]. In vitro studies suggest some effectiveness against ESBL-producing E. coli, particularly in combination with another agent such as amoxicillinclavulanate [54].…”
Section: Mild or Uncomplicated Mdr Utimentioning
confidence: 99%
“…A total of 378 urine cultures from children with pyelonephritis were assessed in a study aimed at the determination of the optimal oral treatment options in children with UTIs. 24 Importantly, the most common organism in children in the 0 to 16 age group was E.coli (85%). Among the antibiotics used in the study, the lowest resistance rates in 378 isolates were observed against pivmecillinam and amoxicillin-clavulanate (6.9 and 7.2%, respectively).…”
Section: Discussionmentioning
confidence: 99%